Pengembangan Modul Sistem Bahan Bakar Bensin Karburator Pada Siswa Kelas XI Teknik Kendaraan Ringan: Pengembangan Modul Sistem Bahan Bakar Bensin Karburator Pada Siswa Kelas XI Teknik Kendaraan Ringan SMK Diponegoro Depok Sleman - Muhammad Mustajab; Setuju Setuju; Diana Ratnawati (JURNAL VOKASI DEWANTARA (JVD), 2022)
This study aims to: (1) determine the module development process, (2) determine the feasibility and (3) determine the effectiveness of the Carburetor Fuel System module, which has been made to support learning in the training eye to interpret technical drawings. The method used in this research is development research method. Data collection techniques in this study used questionnaires and test questions. Meanwhile, the data analysis technique was carried out using descriptive analysis techniques, namely by analyzing quantitative data then interpreted in a qualitative sense. The results showed that: (1) the process of developing the learning module was carried out in four main stages, namely analyzing needs, designing and making modules, testing the feasibility and testing the effectiveness of the modules; (2) Based on the results of the material expert's assessment on the content aspect, the mean score was 2.85 on the eligibility criteria. In the presentation aspect, it was obtained a mean score of 2.07 on the inadequate criteria. In the aspect of language selection, a mean score of 3 is obtained on the feasible criteria; (3) The score is in the score range between> 2.50 to 3.25 on the feasible criteria. Thus, it can be explained that the results of the media expert's assessment on the display aspect are quite feasible.